Alocação ótima de geração distribuída em sistemas de distribuição considerando incertezas no modelo probabilístico de geração - Pereira, Luan Diego de Lima (2018)
This dissertation proposes a methodology to determine a probabilistic model of distributed generation of electrical energy from wind generators and photovoltaic panels and to determine the optimal location of these generators in a distribution network of electric energy, based on technical and economic parameters. The methodology correlates the historical wind speed and solar irradiance data of a particular study region and applies the Monte Carlo simulation to model the power of wind and solar generation, preserving its stochastic nature. The optimization of the location of the distributed generation units aims to minimize the annual losses of active power and the installation costs of the generators connected to the network. The optimization problem also provides for the allocation of capacitor banks in conjunction with the distributed generators, in order to manage the reactive power of the network and, consequently, to improve the voltage profile and minimize the electrical losses. The optimization algorithm used was the Genetic Algorithm, which receives as input the annual data of active power of the wind generators, solar and the demand of the load and search for better solutions to the problem. In order to validate the effectiveness of the proposed model, tests were performed on two real radial feeders, resulting in annual losses of active power, voltage profiles and total investment cost.